From Rationality to Rationalities: The Modern Epistemological Situation in Science and Culture - Dodonova, Vira; Chekal, Lydmyla; Kultenko, Valentyna; Suprun, Alina (Вісник гуманітарних наук, 2026)
The article provides a philosophical analysis of the evolution of the concept of rationality in the context of the crisis of the classical understanding of Reason as a universal and all-encompassing principle of cognition and activity. The “disenchantment with Reason,” caused by its limited capacity to respond adequately to the challenges of historical and social development, has led to a transition from a monistic model of rationality to a pluralistic understanding of it as a multiplicity of types and forms. It is substantiated that the introduction of the concept of the “type of rationality” reflects an aspiration to extend rationalist analysis beyond scientific knowledge and to encompass a broader range of sociocultural practices. The main typologies of rationality proposed by leading philosophers of the twentieth century are examined, and their methodological multidimensionality and historical conditionality are revealed. Particular attention is devoted to Karl-Otto Apel’s concept of communicative and discursive rationality as an attempt to overcome the limitations of instrumental–strategic thinking and to affirm the ethical dimension of rationality. It is concluded that contemporary philosophy of rationality requires not only further typologization but also the theoretical mediation of competing rationalities in order to form a more holistic and responsible vision of human coexistence under conditions of globalization.